Information, International Substitutability, and Globalization - Rauch, James E; Trindade, Vitor (American Economic Review, 2003)
Improved information allows home firms to rule out more potential foreign trade partners in advance of attempting to form a match. The increased responsiveness to country wage or goods price differentials resulting from this better first cut causes the general-equilibrium elasticity of substitution between national labor forces or the Armington elasticity of substitution between domestic and imported output to increase. Further results include an increase in the elasticity of domestic labor demand, an increase in the extent to which reductions in conventional trade barriers equalize national wages, and reduced “natural protection” for domestic producers.